Abstract Book of The Meeting of the Polish Zebrafish Society - Migocka-Patrzałek, Marta
“Abstract Book of The Meeting of the Polish Zebrafish Society” zawiera streszczenia wystąpień ustnych oraz doniesień naukowych zaprezentowanych w formie plakatów naukowych podczas „Meeting of the Polish Zebrafish Society”, które miało miejsce w Warszawie 26-27 września 2019.
Keywords: astroglia; permeability; blood-brain barrier; neurodevelopmental disorders; Tuberous Sclerosis Complex; anxiety; Potassium channel; kcng4b; ear; development; McArdle disease; glycogenolysis; Pygmies; zebrafish; hearing loss; knock-down model; wfs1 gene; Zebrafish Infection Bacteria Pneumococcus Autophagy; Tilapia Lake Virus; anti-viral immune response; interferons type I; DExD/H-box RNA helicases; interferons; vig-1; SVCV; CSV; oral pathogen; host-pathogen interaction; cardiovascular disease; SL-327; acute toxicity; locomotion; Doxorubicin; chemotherapeutic agent; toxicity; glycogen phosphorylase; skeletal muscle tissue; ultrastructure